Agonist selectivity in the oxytocin/vasopressin receptor family: new insights and challenges. (20th July 2007) - Chini, B.; Manning, M.
Abstract : The design and development of selective agonists acting at the OT (oxytocin)/AVP (vasopressin) receptors has been and continues to be a difficult task because of the great similarity among the different receptor subtypes as well as the high degree of chemical similarity between the active ligands. In recent decades, at least a thousand synthetic peptides have been synthesized and examined for their ability to bind to and activate the different OT/AVP receptors; an effort that has led to the identification of several receptor subtype-selective agonists in the rat. However, owing to species differences between rat and human AVP/OT receptors, these peptides do not exhibit the same selectivities in human receptor assays. Furthermore, the discovery of receptor promiscuity, which is the ability of a single receptor subtype to couple to several different G-proteins, has led to the definition of a completely new class of compounds, referred to here as coupling-selective ligands, which may activate, within a single receptor subtype, only a specific signalling pathway. Finally, the accumulating evidence that GPCRs (G-protein-coupled receptors) do not function as monomers, but as dimers/oligomers, opens up the design of another class of specific ligands, bivalent ligands, in which two agonist and/or antagonist moieties are joined by a spacer of the appropriate length to allow the simultaneous binding at the two subunits within the dimer. The pharmacological properties and selectivity profiles of these bivalent ligands, which remain to be investigated, could lead to highly novel research tools and potential therapeutic agents.